Density surface modeling of European hare in the Argentinean Pampas - Gorosabel, Antonella (2022)
The European hare (Lepus europaeus) is a game species with high economic importance for being one of the main exports of wildlife products in Argentina. However, it is also considered an agricultural pest. This study aimed to identify the main environmental, human, and landscape variables influencing the European hare density, and to build density maps in the reproductive and non-reproductive seasons of 2016 and 2017 in the Pampas region. We performed spotlight counts at night and estimated its density using density surface models (DSMs). During the non-reproductive season, we found more individuals in the proximity to the Mar Chiquita Biosphere Reserve and tree plantations; and areas near towns and low accessibility (low road density). While during the reproductive season, we found significantly more European hares in heterogeneous environments, such as areas with smaller crop fields, and with higher mean productivity. In both seasons, we found a significant effect of the geographic coordinates. Based on the best models, we predicted a total abundance of 39,034 and 33,373 European hares, in the non-reproductive and reproductive season respectively. Our results revealed that disturbance by human activities and landscape configuration influenced the spatial variation of European hare density. In this study, by combining land-use changes using remote sensing products, GIS, and considering imperfect detection with distance sampling, we provided an accurate spatial European hare density estimation, which is crucial to develop integrative management programs.